Beyond Language Anxiety - Mihaljević Djigunović, Jelena (Array, 2004)
The article focuses on the relationship of language anxiety and a number of other individual difference variables. In order to understand the role of language anxiety in second language acquisition and behaviour, the author describes a study in which she tried to check the validity of five hypotheses based on findings of previous studies. She looks into the correlations of the included individual difference variables with language anxiety and with foreign language achievement and self-assessment of foreign language skills. Only one of the hypotheses was confirmed by her findings. She concludes that the impact of anxiety on language learning and use should be reconsidered and suggests some directions for future research